2016
DOI: 10.1016/j.trd.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The cumulative effect of nuisances from road transportation in residential sectors on the Island of Montreal – Identification of the most exposed groups and areas

Abstract: The cumulative effect of nuisances from road transportation in residential sectors on the Island of Montreal-Identification of the most exposed groups and areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 93 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Finally, while the simultaneous analysis of exposure to air pollution and noise with the same methodology is a strength of our analysis, the two environmental indicators were still modeled separately. There exist several interesting attempts that assessed the cumulative effect of air pollution and noise (Carrier, Apparicio, Séguin, & Crouse, 2016), examined the trade-off between accessibility and (traffic-related) air pollution (da Schio, Boussauw, & Sansen, 2018) or combined a range of nuisances and urban amenities in one environmental equity indicator (Carrier et al, 2016, Pearce et al, 2010). In this vein, the data in our analysis could form the basis for a wider environmental equity analysis for Ghent.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, while the simultaneous analysis of exposure to air pollution and noise with the same methodology is a strength of our analysis, the two environmental indicators were still modeled separately. There exist several interesting attempts that assessed the cumulative effect of air pollution and noise (Carrier, Apparicio, Séguin, & Crouse, 2016), examined the trade-off between accessibility and (traffic-related) air pollution (da Schio, Boussauw, & Sansen, 2018) or combined a range of nuisances and urban amenities in one environmental equity indicator (Carrier et al, 2016, Pearce et al, 2010). In this vein, the data in our analysis could form the basis for a wider environmental equity analysis for Ghent.…”
Section: Discussionmentioning
confidence: 99%
“…Road traffic [15][16][17] is often the main source of air pollution in urban areas, so it is increasingly necessary to accurately estimate its contribution to urban air pollution. Therefore, many institutions have developed emission models and systems to predict the contribution of road transport to air pollution.…”
Section: Intelligent Transportation Systems and Traffic Pollutionmentioning
confidence: 99%
“…This research has shown an inverse relationship between the level of noise pollution and the distance of the bikeway from the road edge. Moreover, in another research study conducted by Carrier et al ( 2016 ), air pollutions (especially NO 2 ) and noise pollution on the residents of the city of Montreal were evaluated. This study showed that 460 blocks of the studied areas had poor conditions and the people aged 65 years and over were the group most significantly affected.…”
Section: Introductionmentioning
confidence: 99%